Resilient teaching in the northeast of Thailand—Emotional dynamics and performance in private education - Thi Ha, Kyaw; Rodrigo, Russell (Humanities, Arts and Social Sciences Studies, 2024)
Examining the emotional well-being of teachers in Thailand’s private school sector provides significant insights into the dynamics of educational environments. Utilising a cross-sectional quantitative approach, this study investigates the emotional landscapes, attitudes, and coping methods of 109 teachers and 155 students in the Northeast region. This study highlights a young demographic among teachers, an indicator of a call for much inclusivity, particularly LGBTQIA+ representation, and an increase in male educators. The results revealed the teachers’ nuanced perceptions regarding instructional challenges and aspirations, with age, marital status, years of experience, and school size notably shaping these perspectives. Teachers principally reported lower levels of negative emotions. However, a significant concern was exhaustion, pointing to the urgent need for coping strategies to mitigate student disengagement and boost teaching efficacy. The study’s findings underscore the pressing need for these coping strategies, such as relaxation, communication, social support, and mindfulness, signalling the significance of both personal and communal support systems in navigating teaching stress. The study critically identifies significant correlations highlighting the interconnectedness between teachers’ emotions and attitudes and the impact of the school or work environment on performance. These results could influence the global discussion on educators’ health and well-being. This could urge re-evaluation of educational policies and advocacy for in-depth support systems that prioritise teachers’ well-being, thus fostering a transformative educational environment marked by enhanced teacher resilience and improved academic outcomes.